2017
DOI: 10.12965/jer.1734898.449
|View full text |Cite
|
Sign up to set email alerts
|

Changes in gait kinematics and muscle activity in stroke patients wearing various arm slings

Abstract: Stroke patients often use various arm slings, but the effects of different slings on the joint kinematics and muscle activity of the arm in the gait have not been investigated. The effects of joint kinematics and muscle activity in the gait were investigated to provide suggestions for gait training for stroke patients. In all, 10 chronic stroke patients were voluntarily recruited. An eight-camera three-dimensional motion analysis system was used to measure joint kinematics while walking; simultaneously, electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The difference with respect to published results of McAndrew Young et al 42 could be related to the different extraction of the CoM, which in McAndrew Young et al 42 refers only to the lower limbs, not taking into account the upper limbs and trunk that play an important role during walking. 44,45 Dynamic balance indices during level walking were significantly larger in males compared to females. This finding suggests that dynamic balance is a sex-specific variable, and this is in line with studies that have found sex-specific differences in gait patterns.…”
Section: Discussionmentioning
confidence: 95%
“…The difference with respect to published results of McAndrew Young et al 42 could be related to the different extraction of the CoM, which in McAndrew Young et al 42 refers only to the lower limbs, not taking into account the upper limbs and trunk that play an important role during walking. 44,45 Dynamic balance indices during level walking were significantly larger in males compared to females. This finding suggests that dynamic balance is a sex-specific variable, and this is in line with studies that have found sex-specific differences in gait patterns.…”
Section: Discussionmentioning
confidence: 95%
“…Since one of the primary goal of rehabilitation is to make patients independent, very often the training performed immediately after the stroke is focused on the recovery of walking. However, arm skills are also fundamental not only for activities that require fine movements such as grasping, manipulation, functional use of objects, but also for global abilities such as walking and balance reactions 3 , 4 . Furthermore, the non-recovery of the upper limb, which is often persistent, causes disabling conditions and is a major contributor to the reduced quality of life 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Grau-Pellicer et al [14] reported that the walking speed is an important factor for regaining independent outdoor ambulation in community mobility. Hwang and Yoon [15] reported the effects of sling immobilization of the affected extremity on muscle activity and kinematic data of lower extremity rather than clinical walking parameters such as speed. Taken together, these findings suggest that the effects of upper extremity immobilization and consequent walking speed on spatiotemporal gait parameters in stroke patients with hemiparesis have not been reported.…”
Section: Introductionmentioning
confidence: 99%